Quality Practitioners’ Differing Perspectives on Future Software Quality Assurance Practices - Lagstedt, Altti; Dirin, Amir; Williams, Päivi (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Constant changes in a business context and software development make it important to understand how software quality assurance (SQA) should respond. Examining SQA from supplier and client perspectives, this study explores how different groups of SQA practitioners perceive future needs. A survey (n = 93) conducted in fall 2017 explored the views of SQA organizations on future trends. The results indicate that SQA organizations differ slightly in their attitudes to quality categories, as do different groups of SQA practitioners. It is argued that these differences should be taken into account when developing and implementing future SQA strategy. It is further argued that the found basic enables SQA management, evaluation of new practices, and allocation of resources to ensure that all quality categories remain balanced in the future.